Essential Oil Compositions and Antimicrobial Activities of Thymbra spicata L. var. spicata L., Lavandula X Intermedia Emeric ex Loisel., Satureja macrantha C. A. MEYER and Rosmarinus officinalis L. - Karaka, Özgür; Bekler, Fatma Matpan (INST TECNOLOGIA PARANA, 2022)
Medicinal and aromatic plants have been widely using in folk medicine as antimicrobial, antiinflammatory and antinociceptive agents. The aim of this study was to determine essential oil composition and antimicrobial activity of T. spicata, L. X Intermedia, S. macrantha and R. officinalis. Essential oil components of these plants were obtained by water vapor distillation method using Neo-Clevenger apparatus. Essential oil components were determined by gas chromatography-mass spectroscopy (GC-MS). The main components of these plants are carvacrol (74.26 %) and γ-terpinene (10.28%) in T. spicata, 1,8- cineol (32.48%), linalool (24.38%) and camphor (14.73%) in L. X Intermedia, p-cymene (56.70%), carvacrol (10.96 %) in S. macrantha and camphor (18.26 %), α-pinene (15.51%), 1,8-cineole (11.86%) and borneol (10.39%) in R. officinalis were determined. T. spicata and S. macrantha showed strong effects against three microorganisms. L. X Intermedia and R. officinalis showed strong activity against Candida albicans, while they had moderate effects against Staphylococcus aureus, Escherichia coli.
Keywords: Medicinal and aromatic plants; Essential oils; Major compounds; GC-MS